What are the Expectations of Primary School Teachers from Instructional Leaders during the Distance Education Period? - Muhammet Emre Kılıç (Athens Institute for Education and Research, 2022)
The aim of this research is to determine primary school teachers' expectations from instructional leaders during the distance education period. In this study, which was formed in the context of qualitative research method, the case study was used. The participants of this study consist of 11 teachers who worked in primary schools during the 2020-2021 academic term. This data collection tool consisting of 5 questions was prepared as a semi-structured interview form. As a result of the research, the themes of vision, mission, education programs, supervision, school culture and professional development were found, and sub-themes formed depending on these themes were specified.